The Impact of Minimum Wage and Population Growth on Poverty Levels in Sumatera Utara (2016–2025) - Era Sulastri Hutasoit; Marshanda Siburian; Cheresentia Situmorang (International Journal For Advanced Research, 2026)
Economic development in North Sumatra was challenged by persistent fluctuations in poverty levels, indicating structural constraints in achieving inclusive growth. This study examined the effects of minimum wage and population growth rate on the number of people living in poverty in North Sumatra during the 2016–2025 period. The research employed a quantitative approach using secondary time-series data obtained from official statistical publications. Multiple linear regression analysis was conducted, supported by classical assumption tests, to ensure the validity of the model. The results showed that the minimum wage had a negative and statistically significant effect on poverty, indicating that increases in wages contributed to improving purchasing power and reducing the number of poor people. In contrast, the population growth rate did not show a statistically significant partial effect on poverty, suggesting that demographic changes alone were not the primary determinant of poverty levels. However, when analyzed simultaneously, minimum wage and population growth rate had a significant combined effect, explaining 72.8% of the variation in poverty levels. These findings highlighted that poverty reduction in North Sumatra was more strongly influenced by economic policy related to income distribution rather than demographic factors alone. The study emphasized the importance of integrated policy approaches that combine wage regulation with effective population management to achieve sustainable poverty alleviation.